EGG QUALITY AND HATCHABILITY OF In situ - REARED KEDU AND CEMANI HENS FED DIET OF FARMER FORMULATION SUPPLEMENTED WITH VITAMIN E - Wahyuni, H.I.; Suthama, N.; Mangisah, I.; Sarjana, T.A. (Diponegoro University, 2011)
The aim of study was to evaluate the effect of dietary vitamin E supplementation in Kedu andCemani hens reraed in situ and given farmer-formulated diet on egg performances. A total of 120 femaleand 24 male birds were equally divided into two groups of Kedu and Cemani, with average body weightof 1890+216.79 and 1830+396.23 g, respectively. Basal ration was based on the diet formulated by thefarmer (R1) consisting of corn (30%), rice bran (50%), protein concentrate (15%), and premix (5%).Dietary treatments evaluated were R1 (without additional vitamin E), and the other three were theinclusion of DL α-tocopheryl acetate into the R1 diet up to 2 (R2), 4 (R3) and 6 IU (R4). The experimentwas arranged in a Randomized Block Design with 4 treatments, and 2 different groups of hen (Kedu andCemani) were assigned as block. Parameters observed were feed consumption, hen day production, feedconversion ratio, egg quality, fertility, and hatchability. The result showed that vitamin Esupplementation did not affect whatever parameters, except egg fertility. Egg hatchability between Keduand Cemani hens was significantly different (p<0.05). Trend comparison test indicated significantlylinear (p<0.05) for fertility and hatchability. In conclusion, vitamin E supplementation up to 6 IUincreased linearly egg fertility and hatchability of about 5-8%, and egg hatchability of Kedu hens washigher (11%) than that of Cemani.